The Effects of ChatGPT Use and Self Regulated Learning on Students' Critical Thinking Skills: Evidence from the Faculty of Teacher Training and Education, Ekasakti University - Ayu Oktaviani; Caterina Lo; Serli Diovani Teza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed higher education, particularly through the use of ChatGPT as a learning support tool. However, the extent to which AI ChatGPT usage and self-directed learning influence students' critical thinking skills remains unclear. Therefore, this study aimed to examine the effects of AI ChatGPT usage and self-directed learning on the critical thinking skills of students at the Faculty of Teacher Training and Education, Universitas Ekasakti. This study employed a quantitative approach using a survey method. The population consisted of 277 students, with 164 respondents selected through non-probability sampling using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The findings revealed that AI ChatGPT usage had a positive and significant effect on critical thinking skills (t = 2.086; p = 0.039 < 0.05), whereas self-directed learning had no significant effect (t = 1.381; p = 0.169 > 0.05). Simultaneously, AI ChatGPT usage and self-directed learning significantly influenced students' critical thinking skills (F = 3.244; p = 0.042 < 0.05). The coefficient of determination (R²) was 0.039, indicating that the independent variables explained 3.9% of the variance in critical thinking skills, while 96.1% was explained by other factors outside the scope of this study.